Discussing Metaphor as a Pedagogical Practice: Reflections on a Conference Salon - Frankowski, Alicja; Johnston, Lisa (YU-WRITE: Journal of Graduate Student Research in Education, 2022)
In this paper, we reflect on our process of preparing for a salon presentation at the York Graduate Students in Education re: conference. We describe our choice of a salon format to open a critical and interdisciplinary dialogue about the ways we struggle with metaphor as white settlers. We share the content of our salon discussion and explore how metaphor can manifest as an act of transformation in early childhood education. Specifically, we conceptualize our metaphor of early childhood praxis as a Frankensteinian monster, pieced together from mostly psychological theories of child development into a harmonized body of knowledge. As we describe our preparation for the salon, we attend to our inspiration for engaging in aesthetic invitations for dialogue through creative writing, spoken word, mixed media collage, and audio/visual recording. We end with an invitation for continued dialogue on the use of metaphor and its cautions.